2019
DOI: 10.1016/j.eururo.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bladder Stones in Adults and Children: A Systematic Review and Meta-analysis on Behalf of the European Association of Urology Urolithiasis Guideline Panel

Abstract: Bladder stones (BS) constitute 5% of urinary stones. Currently, there is no systematic review on their treatment. Objective: To assess the efficacy (primary outcome: stone-free rate; SFR) and morbidity of BS treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 38 publications
1
38
0
4
Order By: Relevance
“…All of the included patients achieved stone-free status by one session in all type of endoscope (cystoscope and nephroscope) and fragmentation equipment (ultrasonic, pneumatic or both) used during surgery. Donaldson et al reported that the SFR of TUCL was the same with OC, PCCL and higher than ESWL [10].…”
Section: Discussionmentioning
confidence: 94%
“…All of the included patients achieved stone-free status by one session in all type of endoscope (cystoscope and nephroscope) and fragmentation equipment (ultrasonic, pneumatic or both) used during surgery. Donaldson et al reported that the SFR of TUCL was the same with OC, PCCL and higher than ESWL [10].…”
Section: Discussionmentioning
confidence: 94%
“…Transurethral cystolithotripsy (TUCL) is the choice of current interventions for bladder stones in adults and children [1,2]. Although it has the same e cacy as percutaneous cystolithotripsy (PCCL) and shorter hospital stay than PCCL, complications could occur [1,[3][4][5]. A rare complication of bladder rupture with stone slipping out would be encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Alrededor de 1 millón de personas con sospecha de litiasis urinaria acuden a los servicios de emergencia cada año en los Estados Unidos de Norteamérica (4) , los hombres experimentan cólicos renales en una proporción de 2:1 en comparación con las mujeres (3) . El dolor es el principal motivo de admisión en estos pacientes, una vez formado el cálculo, el tamaño y la ubicación del cálculo tiene el mayor efecto sobre los síntomas y el manejo del paciente (6)(7)(8) .…”
Section: Introductionunclassified